Proper Hand Washing for Food Handlers - Amy Simonne (EDIS, 2006)
Hand washing is one of the primary methods used to help prevent foodborne illness. Proper hand washing will reduce your risk of transmitting disease-causing microorganisms such as bacteria, viruses, and other agents to people who eat the food you handle. If you need to use hand sanitizer, always wash your hands first! Dirt, foods, or anything else on your hands makes the alcohol less effective. Do not use hand sanitizer in place of hand washing! This document is FCS 8784-Eng, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date November 2005.